Jesaja 36-39 - Sinkroniese en diakroniese lees van ’n teks - Roux, J. H. le (Verbum et ecclesia, 2002)
Isaiah 36-39 - Sinchronic and diachronic reading of a text. There has been growing interest in the book of Isaiah, particularly with regard to the unity of the book. The current debate has grown out of the discontent of more and more researchers with the historical-critical methods and their results. The classical tripartition of Duhm, and especially his supporters’ application of it, is being queried. The unity of all 66 chapters of Isaiah is indicated as an alternative. The synchronic and diachronic approaches to the text are often played off against each other. An attempt is made to raise questions about both perspectives, showing that each approach has its shortcomings. However, by looking at the text from a diachronic as well as a synchronic perspective, an improved view of the rich variety of the text can be seen. In this article, Isaiah 36-39 serves as an illustration.